2007
DOI: 10.1177/117762500700100020
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Initiation by Mix and Match Elements: Flexibility for Polymerase Binding to Bacterial Promoters

Abstract: Bacterial RNA polymerase is composed of a core of subunits (β, β′, α1, α2, ω), which have RNA synthesizing activity, and a specificity factor (σ), which identifies the start of transcription by recognizing and binding to sequence elements within promoter DNA. Four core promoter consensus sequences, the −10 element, the extended −10 (TGn) element, the −35 element, and the UP elements, have been known for many years; the importance of a nontemplate G at position −5 has been recognized more recently. However, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
212
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 115 publications
(221 citation statements)
references
References 156 publications
(334 reference statements)
6
212
3
Order By: Relevance
“…1C). Our previous work demonstrated that P minor and P min belong to a newly identified promoter class, Ϫ 35/TGn, that is characterized by a requirement for both an excellent Ϫ35 element and an extended Ϫ10 TGn sequence to compensate for a poor Ϫ10 element (1,37,38). To investigate whether the effect of region 1.1 with P minor reflects a general characteristic of Ϫ35/TGn promoters, we compared the formation of active transcription complexes at P min with that at P min16 , a derivative with perfect Ϫ35 and Ϫ10 elements, and at P min7 , a derivative with a good Ϫ35 and a perfect TGn and Ϫ10 element (Fig.…”
Section: Effectmentioning
confidence: 99%
See 2 more Smart Citations
“…1C). Our previous work demonstrated that P minor and P min belong to a newly identified promoter class, Ϫ 35/TGn, that is characterized by a requirement for both an excellent Ϫ35 element and an extended Ϫ10 TGn sequence to compensate for a poor Ϫ10 element (1,37,38). To investigate whether the effect of region 1.1 with P minor reflects a general characteristic of Ϫ35/TGn promoters, we compared the formation of active transcription complexes at P min with that at P min16 , a derivative with perfect Ϫ35 and Ϫ10 elements, and at P min7 , a derivative with a good Ϫ35 and a perfect TGn and Ϫ10 element (Fig.…”
Section: Effectmentioning
confidence: 99%
“…1). In addition, structures of , core polymerase, and holoenzyme from thermophilic bacteria (4,(24)(25)(26)(27)(28)(29) or portions of E. coli 70 (30,31) have provided 3D scaffolds on which to model these steps.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Transcription initiation proceeds through multiple steps (Kontur et al, 2008;Saecker et al, 2002; reviewed by Hook- Barnard & Hinton, 2007), from an initial closed complex (RP C ), in which the DNA is fully double-stranded, to an open complex (RP O ), in which polymerase has isomerized and the DNA has bent, opened and descended into the active site (Gries et al, 2010). Consequently, there are multiple points at which an activator might function.…”
Section: Bacterial Transcription Activation Occurs Through a Variety mentioning
confidence: 99%
“…In primary s factors, which are responsible for most transcription during exponential growth, four conserved regions (regions 1-4) mediate interactions between s and the core and/or promoter specificity (reviewed by Hook- Barnard & Hinton, 2007). Regions 2, 3 and 4 bind to specific recognition sites in the promoter DNA: the 210 element ( -12 TATAAT -7 ), an extended -10 element ( -15 TG -14 ) and the 235 element ( -35 TTGACA -30 ), respectively.…”
Section: Temporal Gene Regulation By Bvga~p Coordinates the Expressiomentioning
confidence: 99%